Ferroelastic phase transition with large spontaneous strain caused by freezing the conformational dynamics of ammonium. Issue 7 (18th February 2022) - Li, Li-Ting; Ji, Cui-Xian; Sun, Ying-Xi; Jin, Ya-Wei; Ni, Guo-Hao; Sun, Jia-Yue; Han, Rui-Rui; Zhao, Jiong-Peng; Liu, Fu-Chen
Abstract : Through the structural regulation of long chain organic ammonium in a confined space, a ferroelastic phase transition with large spontaneous strain is realized. Abstract : By adjusting the substituent group of the organic ammonium in three molecular ionic complexes, [A][Fe3 O(O2 CH)8 (H2 O)]2 (A = NH3 (CH2 )3 NH3 for 1, CH3 NH2 (CH2 )3 NH3 for 2 and CH3 CH2 NH2 (CH2 )3 NH2 CH2 CH3 for 3 ), crystallized in the 2/ m point group at room temperature with similar structure, conformational transformation-caused dynamic disorder and pseudosymmetry is realized in 3 . When the conformational interchange of the ammonium is frozen, the disorder–order 2/ mF 1̄ ferroelastic phase transition is presented, which leads to dielectric relaxation and a large spontaneous strain of 0.207.